КРИТЕРІЇ, ПОКАЗНИКИ ТА РІВНІ СОЦІАЛЬНО- ПЕДАГОГІЧНОЇ АДАПТАЦІЇ СТУДЕНТІВ З ОСОБЛИВИМИ ОСВІТНІМИ ПОТРЕБАМИ В УМОВАХ ЗАКЛАДУ ВИЩОЇ ОСВІТИ - Гладиш М. О.; Соловйова Т. Г. (World Science, 2019)
Adaptation can take different forms and in some cases, for specific categories of students. Recent views on inclusion have stressed the fact that inclusion is in the first place of the educational reform issue. Inclusion starts from the right of all students to follow higher education. The inclusive educational environment is a fundamental condition of socio-pedagogical adaptation of students with special educational needs at higher education institutions. The statement of the criteria, indicators and levels of the process is an important part of the socio-pedagogical research of adaptation. It allows the different approaches to be narrowly correlated to the current position of inclusive education.